2021
DOI: 10.1371/journal.pone.0259277
|View full text |Cite
|
Sign up to set email alerts
|

Nanopore sequencing of SARS-CoV-2: Comparison of short and long PCR-tiling amplicon protocols

Abstract: Surveillance of the SARS-CoV-2 variants including the quickly spreading mutants by rapid and near real-time sequencing of the viral genome provides an important tool for effective health policy decision making in the ongoing COVID-19 pandemic. Here we evaluated PCR-tiling of short (~400-bp) and long (~2 and ~2.5-kb) amplicons combined with nanopore sequencing on a MinION device for analysis of the SARS-CoV-2 genome sequences. Analysis of several sequencing runs demonstrated that using the long amplicon schemes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
1
16
0
1
Order By: Relevance
“…Thus, the long amplicon protocol appears to be effective in detecting spike variants. Our observation was also supported by a recent publication [ 39 ]. Brejova et al compared the sequencing results obtained from the libraries containing SARS-CoV-2 samples made of 400 bp (primer set I), 2000 bp, and 2500 bp (primer set III) amplicon pools to conclude that sequencing long amplicons clearly outperforms shorter amplicons in terms of lower coverage variation and overall quality of the consensus sequences.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the long amplicon protocol appears to be effective in detecting spike variants. Our observation was also supported by a recent publication [ 39 ]. Brejova et al compared the sequencing results obtained from the libraries containing SARS-CoV-2 samples made of 400 bp (primer set I), 2000 bp, and 2500 bp (primer set III) amplicon pools to conclude that sequencing long amplicons clearly outperforms shorter amplicons in terms of lower coverage variation and overall quality of the consensus sequences.…”
Section: Discussionsupporting
confidence: 92%
“…Oxford Nanopore protocols SARS-CoV2 PCR tailing based are suggested to sequence the coronavirus genome directly from nasopharyngeal or oropharyngeal swabs. In order to cover the whole genome, these protocols, exploiting the technology based on an array of nanopores, use a multiplex primers scheme , which generate longer amplicons and tend to produce close-to-finished genomes more quickly than short reads based sequencing platforms [9]. Moreover, despite a single nanopore long read can have a more relatively higher error rate than short read, studies that compare the genome assembly derived from both technologies demonstrated that through Nanopore it is possible to achieve highly accurate consensus single nucleotide variant (SNV) calling with >99% sensitivity and >99% precision with a minimum of about 60-fold coverage [9].…”
Section: Discussionmentioning
confidence: 99%
“…On other hand, these protocols produce a higher percentage of reads that are not analyzable by the bioinformatic pipelines, likely due to a combination of fragmentation of synthesized molecules and prematurely aborted molecules during sequencing [9]. Brejová et coworkers dissected the genome assembly generated by sequencing of amplicons derived from samples of the same biological material using schemes of primers set, which produced long reads of 400-bp, 2-kb, and 2.5 kb.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples originated from oropharyngeal swabs collected in January 2021. The sample processing and sequencing library construction were carried out as described earlier (Brejová et al, 2021), generally following the COVID-19 virus protocol (PTC 9096 v109 revF 06Feb2020; Oxford Nanopore Technologies, Oxford, UK) with some modifications. After RNA extraction for each sample, SARS-CoV-2 RNA was quantified by an RT-qPCR assay carried on QuantStudio™ 5 Real-Time PCR System (Applied Biosystem, Foster City, California, USA).…”
Section: Methodsmentioning
confidence: 99%